SPATIO-TEMPORAL VARIATION OF THE MARINE PHYTOPLANCTON ON THE ALBACORA PLATFORM, LOT Z1, TUMBES, PERU - Falero-Alama, Sandra (2019)
The present investigation was carried out on the Albacora platform of Lot Z1, 10 nautical miles from the coast of the districts of Corrales and La Cruz, Province of Tumbes - Tumbes, Peru and consisted in evaluating the quarterly spatio-temporal variation of the marine phytoplankton of the year 2014. The environmental variables were taken as sea surface temperature, salinity, pH and dissolved oxygen. 100 samples were collected in total. The phytoplankton samples were collected on the surface, by means of a network of 75 u of opening with a diameter of 20 cm, by surface trawling in a craft fishing vessel at a speed of 3 knots for 5 min. A total of 201 species was recorded between diatoms and dinoflagellates, with diatoms predominating with 119 species. The spatio-temporal variation of the phytoplankton registered greater richness and abundance in stations E-4 (2 km, southwest of the Platform) and E-5 (2 km, southeast of the Platform) during the second quarter at an average surface temperature of 25.5°C, salinity 33.2 UPS, pH 8.1 and Dissolved Oxygen 5.9 mg·L-1, values ​​that are within the water quality standards (ECA), according to DS°002-2008-MINAM (Ministry of the Environment) of Peru. Regarding phytoplankton diversity indices, the dominance of diatoms over dinoflagellates in E-1 stations (500 m northeast of the Platform, in favor of the current), E-2 (500 m northwest) of the Platform, against the current) and E-3 (Plataforma Albacora), was recognized during all the quarters of the year. The presence of Chaetoceros coarctatus Lauder 1864, Guinardia striata (Stolterfoth) Hasle in Hasle & Syvertsen 1996 and Ceratium breve (Ostenfeld & Schmidt) Schröder 1906 related to the increase in temperature and typical of Surface Equatorial Waters (AES) are reported as phytoplankton bioindicators.